Educating Educators in the Age of Trump - Kitzmiller, Erika (Radical Teacher, 2018)
This essay will outline what we did in the 15-week course, Education in the Age of Trump, and will document the ways in which it made us all vulnerable. It will analyze the possibilities and perils of creating an overtly political classroom in an era of political polarization and widespread fear.